Circulating Cytokines Predict 1H-Proton MRS Cerebral Metabolites in Healthy Older Adults - Langer, Kailey; Cohen, Ronald A.; Porges, Eric C.; Williamson, John B.; Woods, Adam J. (Frontiers in Aging Neuroscience, 2021)
Background: Changes in both circulating cytokines and neurochemical concentrations have been observed in aging. Patterns of change across these factors are associated with age-related pathologies, including neurodegenerative disease. More evidence to define patterns of change that are characteristic of healthy aging is needed, as is investigation into how age-related changes in blood cytokines and brain neurochemicals may relate to one another in a healthy older adult population. Methods: Single voxel 1H-proton magnetic resonance spectroscopy was collected in medial frontal and medial parietal regions. Phosphocholine and glycerophosphocholine (Cho), myo-inositol (MI), N-acetylaspertate and N-acetylasperglutamate (NAA), creatine and phosphocreatine (Cr), and glutamate and glutamine (Glx) were measured in a sample of 83 healthy, cognitively normal adults aged 52-89. Blood data were collected to quantify 12 cytokines: interleukins (IL-) 2, 5, 6, 7, 8, 10, 12, 13, IL-1 , tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-), and IL-17 α. Correlation analyses were performed to assess age relationships between each of these factors. Backward linear regressions were performed. Cytokine data and age were used as predictors of each cerebrospinal fluid-corrected metabolite concentration in both voxels. Results: Associations were identified between a variety of cytokines and concentrations of frontal NAA, Cr, and Glx, and of parietal MI, Cho, NAA, and Cr. In the frontal voxel, NAA was predicted by more IL-1B and less TNF-α, Cr by less TNF-α and more IL-5, and Glx by less TNF-α. In the parietal voxel, MI was predicted by more IL-10 and IL-8 and less IL-2, Cho by more TNF-α and less IL-2, NAA by more IL-1B and TNF-α and less IL-13, IL-2, and IL-7, and Cr by more IL-10 and less IL-2. Conclusions: Associations were identified between circulating cytokines and neurometabolite concentrations in this sample of older adults. The present results serve as initial evidence of relationships between circulating cytokines and neurophysiology. Findings invite further investigation to understand the physiological consequences of aging, and how peripheral inflammatory markers may relate to neurochemical concentrations in healthy aging.